2006
DOI: 10.1055/s-2006-949517
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Decompression for Orbitofrontal Fibrous Dysplasia: Recent Development of Surgical Technique and Equipment

Abstract: Objectives: Orbitofrontal fibrous dysplasia often involves the bony orbit and optic canal. Although fibrous dysplasia reportedly produces compression of the optic nerve leading to visual disturbances, optic nerve decompression in patients without clinical signs of optic neuropathy remains controversial. We describe the recent development of surgical techniques and equipment for optic nerve decompression in orbitofrontal fibrous dysplasia. Methods: Optic nerve decompression was performed prophylactically for fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…There is literature available on treatment of patients with optic nerve injuries using a high dose of hormones and certain satisfactory results achieved in it, but according to the statistics, the effectiveness of this single medication treatment was much lower than that of comprehensive treatment with the surgery as the main therapy [10,[13][14][15][16][17][18][19][20][21][22]. In addition to that, patients with OAS were severely injured and the orbital apexes and the optic canals were obviously compressed by the fractures; therefore, surgical procedures are very necessary to treat OAS [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…There is literature available on treatment of patients with optic nerve injuries using a high dose of hormones and certain satisfactory results achieved in it, but according to the statistics, the effectiveness of this single medication treatment was much lower than that of comprehensive treatment with the surgery as the main therapy [10,[13][14][15][16][17][18][19][20][21][22]. In addition to that, patients with OAS were severely injured and the orbital apexes and the optic canals were obviously compressed by the fractures; therefore, surgical procedures are very necessary to treat OAS [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Optic nerve decompression is generally recommended only in orbital involvement causing symptomatic optic nerve impingement. 1,20,22 A retrospective review by Abe et al 20 suggested that the unilateral frontotemporal extradural approach for decompressive surgery as seen in our patient may be superior to other approaches.…”
Section: Discussionmentioning
confidence: 72%
“…19 Other theories regarding the pathogenesis of visual impairment in FD have been proposed, including traction on the optic nerve, spontaneous hemorrhage, and external compression of optic canal contents by a separate cystic lesion, such as a mucocele. 10,13,15,18,20 Growth hormone excess in FD has also been associated with optic neuropathy. Therefore, screening for growth hormone excess should be done in all patients with craniofacial FD as it is treatable.…”
Section: Discussionmentioning
confidence: 99%
“…ONC can result from primary CFD of the sphenoid bone or from secondary lesions, including cystic FD, mucoceles, hemorrhage, and aneurysmal bone cysts [27]. While there is consensus that therapeutic decompression of the optic nerve is indicated for symptomatic patients, the question of whether to operate on asymptomatic patients is an ongoing controversial issue [6,8,13,36]. Earlier studies had reported visual impairment in 20-80% of patients with ONC [19,23].…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for study population inclusion were histopathologic diagnosis of CFD, radiologically confirmed optic canal narrowing, pre-and post-treatment visual status (based on visual fields and visual acuity), and .4 months of follow-up. The included studies are listed in Tables S1, S2, S3 (supplementary material) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. Follow-up included periodic (6-12 months) radiological imaging with CT and MRI as well as ophthalmologic exams.…”
Section: Participantsmentioning
confidence: 99%